Multiples of multiple: Case series of mirror aneurysms and review of literature. (2019) - Rajagopal, Niranjana; Yamada, Yasuhiro; Balaji, Arun; Kawase, Tsukasa; Kato, Yoko
Highlights: Incidentally detected unruptured mirror intracranial aneurysms are on the rise due to advanced imaging modalities. Further studies are required to elucidate theories of development, inheritance pattern and the need for screening of 1st-degree relatives with twin aneurysms. Treatment strategy for mirror aneurysms should be customised based on the location, size, morphology and clinical manifestations of each patient. Randomised control trials that compare [single/multistage] clipping and coiling of mirror aneurysms are necessary to decide the best intervention strategy. Abstract: Introduction: Mirror aneurysms are a rare subtype of multiple aneurysms, located in identical or adjacent arterial segment bilaterally. We report a case series of 3 such patients amongst whom one of them had 3 sets of mirror aneurysms and the other patient had 2 sets of mirror aneurysm on the same arterial segment which has not been reported till date. Methods: A retrospective analysis of 3 patients with incidentally detected multiple mirror aneurysms, who were treated with microsurgical clipping and coiling, was conducted. A systematic search was performed using the PUBMED database and relevant articles were reviewed with particular attention to incidence, associated conditions, risk factors and management strategies. Written informed consent was obtained from all of the patients for publication of this case report and accompanying images. A copy of the written consent is available for review by the Editor-in-Chief of this journal on request. This research work has been reported in line with the PROCESS criteria (Agha et al., 2018). Results: All the 3 patients were females with incidentally detected multiple mirror aneurysms. All the 3 patients were known Hypertensives. All the aneurysms were successfully clipped by a multistage, bilateral craniotomy except the one in the cavernous ICA, for which an endovascular procedure is planned. All of them had an uneventful postoperative course with the CT angiogram showing obliteration of all the clipped aneurysms except the one in the cavernous ICA. Conclusions: Multiple mirror aneurysms represent a rare occurrence of a diverse pathology. Both these described types of cases have not been reported so far in the literature. The treatment strategy for mirror aneurysms should be determined individually based on the location, size, and morphology of the aneurysms, as well as, on the clinical manifestations of each patient.